Post-glacial reactivation of the Bollnäs fault, central Sweden – a multidisciplinary geophysical investigation - Malehmir, Alireza; Andersson, Magnus; Mehta, Suman; Brodic, Bojan; Munier, Raymond; Place, Joachim; Maries, Georgiana; Smith, Colby; Kamm, Jochen; Bastani, Mehrdad; Mikko, Henrik; Lund, Björn (Solid Earth, 2016)
Glacially induced intraplate faults are conspicuous in Fennoscandia where they reach trace lengths of up to 155 km with estimated magnitudes up to 8 for the associated earthquakes. While they are typically found in northern parts of Fennoscandia, there are a number of published accounts claiming their existence further south and even in northern central Europe. This study focuses on a prominent scarp discovered recently in lidar (light detection and ranging) imagery hypothesized to be from a post-glacial fault and located about 250 km north of Stockholm near the town of Bollnäs. The Bollnäs scarp strikes approximately north–south for about 12 km. The maximum vertical offset in the sediments across the scarp is 4–5 m with the western block being elevated relative to the eastern block. To investigate potential displacement in the bedrock and identify structures in it that are related to the scarp, we conducted a multidisciplinary geophysical investigation that included gravity and magnetic measurements, high-resolution seismics, radio-magnetotellurics (RMT), electrical resistivity tomography (ERT) and ground-penetrating radar (GPR). Results of the investigations suggest a zone of low-velocity and high-conductivity in the bedrock associated with a magnetic lineament that is offset horizontally about 50 m to the west of the scarp. The top of the bedrock is found ∼ 10 m below the surface on the eastern side of the scarp and about ∼ 20 m below on its western side. This difference is due to the different thicknesses of the overlying sediments accounting for the surface topography, while the bedrock surface is likely to be more or less at the same topographic level on both sides of the scarp; else the difference is not resolvable by the methods used. To explain the difference in the sediment covers, we suggest that the Bollnäs scarp is associated with an earlier deformation zone, within a wide (> 150 m), highly fractured, water-bearing zone that became active as a reverse fault after the latest Weichselian deglaciation.